Semantic determination of the noun - Jalolov Furkat Fattokhovich (Proceedings of The ICECRS, 2019)
English nouns are classified two main groups, such as countable and uncountable nouns. So expressing semantic determination of countable nouns distinguishes from uncountable nouns.